The Study of Financial Problem Among the Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh’s Campus Students - Nurhana; Abu Bakar, Norhaliza; Mohd Khalid, Nur Amirah Auni; Abdullah, Nurul Hanani; Chiun, Celine Chua Miao (Multidisciplinary Applied Research and Innovation, 2020)
In this research, the financial problem among the students of UTHM campus Pagoh is studied. A questionnaire on how the students manage their financial is distributed. The data obtained is analyzed using Statistical Package for the Social Sciences (SPSS) software. The results showed that half of the students expressed an interest to attend financial course in order to overcome their financial problem.